Molecular basis for the genome engagement by Sox proteins. (March 2017) - Hou, Linlin; Srivastava, Yogesh; Jauch, Ralf
Abstract: The Sox transcription factor family consists of 20 members in the human genome. Many of them are key determinants of cellular identities and possess the capacity to reprogram cell fates by pioneering the epigenetic remodeling of the genome. This activity is intimately tied to their ability to specifically bind and bend DNA alone or with other proteins. Here we discuss our current knowledge on how Sox transcription factors such as Sox2, Sox17, Sox18 and Sox9 'read' the genome to find and regulate their target genes and highlight the roles of partner factors including Pax6, Nanog, Oct4 and Brn2. We integrate insights from structural and biochemical studies as well as high-throughput assays to probe DNA specificity in vitro as well as in cells and tissues.